Psychiatric care use among migrants to Sweden compared with Swedish-born residents: a longitudinal cohort study of 5 150 753 people - James B Kirkbride; Christina Dalman; Anna-Clara Hollander; Euan Mackay; Hugo Sjöqvist; Sofie Bäärnhielm (BMJ Global Health)
Background To investigate differences in psychiatric care use over time between Swedish born and those born abroad who migrate to Sweden.Methods Population-based cohort study analysing linked population and health registers, following individuals born 1944–1990 from 1 January 2005 to 31 December 2016. Time-stratified survival analysis using Cox regression estimated time to psychiatric care use. Population included 5 150 753 individuals with 78.1% Swedish born. Migrant status was coded as Swedish born or migrant. Migrants were grouped by year of immigration and region of origin. The main outcome: psychiatric care use, defined as any psychiatric care; psychiatric inpatient or outpatient care; or use of psychotropics.Results Migrants arriving before 2005 had a higher use of any psychiatric care relative to Swedish born but migrants arriving 2005 onwards had lower use. Migrants from sub-Saharan Africa and Asia had a lower use of any psychiatric care during the first decade in Sweden whereas migrants from Middle East and North Africa had a higher use, driven by use of psychotropics.Conclusions The lower use of psychiatric care during the first decade contrasts with higher use among migrants with a longer duration of stay. Psychiatric care use among migrants should be analysed multi-dimensionally, taking duration of stay, region of origin and type of care into account.